Soft and hard carbon composite material and preparation and application thereof

By building a double-sulfur-rich soft and hard carbon composite material, the problems of limited sodium storage capacity and unstable performance of the negative electrode material of sodium ion battery are solved, and the first charging and discharge capacity and cycling performance of the sodium battery are improved.

CN119252886AActive Publication Date: 2025-01-03XIAOGAN CORNEX NEW ENERGY INNOVATION TECHNOLOGY CO LTD

Patent Information

Application Number
CN202411327313.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2025-01-03
Estimated Expiration
2044-09-23

AI Technical Summary

Technical Problem

The existing sodium ion battery negative electrode materials have problems such as limited sodium storage capacity, low Coulomb efficiency for the first time, poor rate performance and unstable cycle performance.

Method used

Using soft and hard carbon composite materials, through the surface chemical modification and pore structure regulation of mesophase carbon microspheres, a double-sulphur-rich core-shell structure is constructed. The core is sulfur-doped mesophase carbon microspheres at the base layer pore carbon, and the outer shell is sulfur Doped PEDOT based hard carbon broadens the carbon layer spacing and increases activated carbon sulfur bonds, improving intercalation capacity and surface capacitance storage.

Benefits of technology

It significantly improves the first charge and discharge capacity, first effect and cycling performance of sodium batteries, achieves the balance of intercalation capacity and surface adsorption capacity, and enhances the migration and diffusion capacity of electrolyte ions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119252886A_ABST
    Figure CN119252886A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of sodium ion batteries, and particularly relates to a soft and hard carbon composite material and preparation and application thereof.The soft and hard carbon composite material is of a double-sulfur-rich core-shell structure with soft carbon coated with hard carbon, the soft carbon serving as an inner core is sulfur-doped mesocarbon microbead-based secondary pore carbon, and the sulfur-doped mesocarbon microbead-based secondary pore carbon serves as an outer core; the hard carbon serving as the shell is sulfur-doped PEDOT (poly (3, 4-ethylenedioxythiophene))-based hard carbon. The core-shell structure is constructed by means of surface chemical modification, pore structure regulation and control, soft and hard carbon compounding and the like of the mesocarbon microbeads, the technical problem that the sodium storage capacity of the pitch-based soft carbon anode needs to be improved is solved, considerable intercalation capacity can be obtained by means of widened carbon layer spacing, and the sodium storage capacity of the pitch-based soft carbon anode can be improved. And abundant sodium storage sites can be obtained to realize large-proportion surface capacitance storage, so that the first charge-discharge capacity, the first efficiency and the cycle performance of the sodium ion battery (sodium battery) are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of sodium ion batteries, and in particular relates to a soft and hard carbon composite material and a preparation and application thereof. Background Art

[0002] In recent years, with the development of large-scale energy storage and electric vehicles, sodium-ion batteries have regained attention due to their abundant raw materials and low cost, becoming one of the options to replace lithium-ion batteries. The positive electrode materials of sodium-ion batteries have borrowed the research results of lithium-ion batteries and made great progress. However, graphite materials, the negative electrode materials of commercial lithium-ion batteries, are not suitable as negative electrode materials for sodium-ion batteries, and carbon materials with larger interlayer spacing have become a new choice for negative electrode materials for sodium-ion batteries.

[0003] Sodium-ion batteries (SIBs) are low-cost alternative energy storage devices to lithium-ion batteries in large-scale power storage systems and electric vehicles. Anode materials (negative electrode materials) are the key to the commercialization of sodium-ion batteries. SIBs anode materials can be divided into five categories: carbon materials, titanium-based materials, alloy materials, metal compound materials and organic matter. Among carbon materials, mesophase carbon microspheres and mesophase asphalt, as phased products of asphalt thermal condensation, have abundant graphite microcrystals and exhibit good conductivity, but have the disadvantages of small carbon layer spacing and few surface defects, resulting in the asphalt-based soft carbon anode The sodium storage capacity is very limited. Hard carbon precursors usually have a natural porous structure and abundant surface functional groups. While contributing to the sodium storage capacity, they also cause many problems such as poor rate performance, low first coulombic efficiency, and sodium metal deposition. Among titanium-based materials, those with low redox potential (Ti 3+ / Ti 4+ ), low lattice stress, low cost, and non-toxic titanium-based compounds are very suitable as SIBs anode materials, but the relatively low specific capacity (<120mAh / g) and first coulombic efficiency are the main problems restricting the commercialization of titanium-based compound anode materials. Alloy and metal compound materials generally exhibit high sodium storage capacity, but the huge volume expansion may lead to poor rate and cycle performance. Organic matter has become an extremely attractive anode material due to its advantages such as multi-electron reaction, adjustable voltage range and low cost. However, the low first coulombic efficiency and poor cycle stability need to be solved urgently.

[0004] In view of this, the present invention is proposed. Summary of the invention

[0005] The purpose of the present invention is to provide a soft and hard carbon composite material and its preparation and application. A soft and hard carbon composite material is constructed by surface chemical modification of mesophase carbon microspheres, pore structure regulation and soft and hard carbon composite. The inner core is soft carbon of sulfur-doped mesophase carbon microsphere-based hierarchical carbon, and the outer shell is sulfur-doped PEDOT-based hard carbon, so as to solve the technical problem that the sodium storage capacity of asphalt-based soft carbon anode needs to be improved. It can not only obtain considerable intercalation capacity by widening the carbon layer spacing, but also obtain abundant sodium storage sites to realize a large proportion of surface capacitance storage, thereby improving the first charge and discharge capacity, first efficiency and cycle performance of sodium ion batteries (sodium batteries).

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] In a first aspect, a soft and hard carbon composite material has a core-shell structure of hard carbon coating soft carbon and being doubly sulfur-rich, wherein the soft carbon as the inner core is sulfur-doped mesophase carbon microsphere-based hierarchical carbon, and the hard carbon as the outer shell is sulfur-doped PEDOT-based hard carbon.

[0008] Further, the carbon interlayer spacing of the soft and hard carbon composite material is 0.340-0.410 nm;

[0009] and / or, the sulfur doping amount of the soft and hard carbon composite material is 6.5 to 8.8 at %;

[0010] And / or, the content of active carbon-sulfur bonds (CSC) in the soft and hard carbon composite material accounts for 96-100% of the sulfur-containing organic bonds.

[0011] Furthermore, the soft carbon is obtained by using sulfur-doped mesophase carbon microspheres obtained by etching the surface of mesophase carbon microspheres with H2S as a precursor, and then modified by sulfur doping and pore adjustment using magnesium sulfate as a sulfur source template and carbonized.

[0012] Furthermore, the addition mass ratio of the magnesium sulfate to the sulfur-doped mesophase carbon microspheres is 1-10:1; and / or the carbonization temperature is 600-890°C.

[0013] In a second aspect, a method for preparing the soft and hard carbon composite material as described in the first aspect comprises the following steps:

[0014] The soft carbon is prepared by using sulfur-doped mesophase carbon microspheres as a precursor, and then carbonized after being modified by sulfur doping and pore adjustment using magnesium sulfate as a sulfur source template, to obtain hierarchical porous carbon based on sulfur-doped mesophase carbon microspheres;

[0015] The soft and hard carbon composite material is obtained by using the soft carbon as the core, guiding the EDOT monomer to oxidatively polymerize on its surface, and then subjecting it to high-temperature inert carbonization, i.e., sulfur-doped PEDOT-based hard carbon;

[0016] The soft and hard carbon composite material has a core-shell structure in which hard carbon covers soft carbon and is doubly sulfur-rich.

[0017] Furthermore, the sulfur-doped mesophase carbon microspheres are prepared by using mesophase carbon microspheres as precursors through pre-oxidation treatment and H2S gas etching.

[0018] Furthermore, when preparing the soft carbon, the added mass ratio of the magnesium sulfate to the sulfur-doped mesophase carbon microspheres is 1 to 10:1.

[0019] Furthermore, when preparing the soft and hard carbon composite material, the added mass ratio of the EDOT monomer and the soft carbon is 1-20:80-99.

[0020] In a third aspect, an application of the soft and hard carbon composite material as described in the first aspect or the second aspect is as follows:

[0021] A sodium negative electrode material comprises the soft and hard carbon composite material or the soft and hard carbon composite material prepared by the preparation method.

[0022] A sodium ion battery comprises the soft and hard carbon composite material or the soft and hard carbon composite material prepared by the preparation method.

[0023] Compared with the prior art, the present invention has at least the following beneficial effects:

[0024] 1. The soft and hard carbon composite materials of the present invention have a dual sulfur-rich core-shell structure, wherein the soft carbon serves as the inner core, which is sulfur-doped mesophase carbon microsphere-based hierarchical carbon, and the hard carbon serves as the outer shell, which is sulfur-doped PEDOT-based hard carbon, thereby achieving an improvement in the sodium storage capacity of the mesophase carbon microspheres. Not only can a considerable intercalation capacity be obtained by virtue of the broadened carbon layer spacing, but also abundant sodium storage sites can be obtained to achieve a large proportion of surface capacitance storage. When applied to sodium batteries, this is beneficial to the improvement of the first charge and discharge capacity, first efficiency and cycle performance.

[0025] In particular, the construction of the core-shell structure unexpectedly achieves the re-sulfur doping of the sulfur-containing soft carbon core to the PEDOT-based hard carbon shell at high temperature, providing additional active sulfur-containing functional groups (active carbon-sulfur bonds CSC) for the PEDOT-based hard carbon while widening the carbon layer spacing. Specifically, the sulfur-doped mesophase carbon microsphere-based hierarchical porous carbon is used as the polymerization center to guide the organic sulfur-containing compound monomer EDOT to polymerize layer by layer on its surface. During the high-temperature inert carbonization process, the sulfur element on the surface of the polymerization center escapes outward in the form of gas while the outer carbon shell is formed, and the outer carbon shell is re-S-doped, making the core-shell structure a double sulfur-rich structure. The sulfur-doped mesophase carbon microsphere-based hierarchical porous carbon core has rich graphite microcrystals and contributes to good conductivity. At the same time, the re-sulfur doping of the PEDOT-based hard carbon shell is achieved, which can not only increase the pseudocapacitance contribution, but also widen the carbon layer spacing and improve the intercalation capacity; and the PEDOT-based hard carbon shell presents a layer-by-layer cross-linked structure, and the soft and hard carbons are in close contact, which is conducive to the full activation of the active sites and the rapid migration and diffusion of electrolyte ions.

[0026] 2. The method for preparing the soft and hard carbon composite materials of the present invention can improve the sodium storage capacity of the mesophase carbon microspheres by surface chemical modification, pore structure regulation and soft and hard carbon composites. It can not only obtain considerable intercalation capacity by broadening the carbon layer spacing, but also obtain abundant sodium storage sites to achieve a large proportion of surface capacitance storage.

[0027] During the preparation process, firstly, mesophase carbon microspheres are selected as precursors, and sulfur is doped once on them through surface modification to obtain sulfur-doped mesophase carbon microspheres; secondly, sulfur-doped mesophase carbon microspheres are used as precursors, and magnesium sulfate is selected as a hard template and sulfur source, and secondary sulfur doping is performed while regulating the mesoporous structure, to prepare sulfur-doped mesophase carbon microsphere-based hierarchical carbon with high sulfur doping and high mesoporosity; thirdly, sulfur-doped mesophase carbon microsphere-based hierarchical carbon is used as the polymerization center, and the organic sulfur-containing compound monomer EDOT is selected to polymerize layer by layer to form a sulfur-containing polymer shell for third sulfur doping; finally, the sulfur-containing polymer shell is carbonized, and the sulfur element on the surface of the polymerization center escapes outward in the form of gas during the high-temperature inert carbonization process, and the sulfur-containing polymer shell is sulfur-doped four times, and finally a soft and hard carbon composite material with a double sulfur-rich core-shell structure with sulfur-doped mesophase carbon microsphere-based hierarchical carbon as the core and sulfur-doped PEDOT-based hard carbon as the shell is prepared.

[0028] Generally speaking, the main charge storage contributions include: diffusion-controlled intercalation process and surface-driven controlled (pseudo) capacitance process. The present invention has multiple sulfur dopings with different methods because different sulfur doping methods will lead to differences in sodium storage mechanisms. The first sulfur doping using H2S etching for sulfur doping can achieve a significant increase in carbon interlayer spacing, sp2 carbon content and sulfur doping amount. Although the first coulomb efficiency (first efficiency) is slightly reduced, the sodium storage performance is significantly improved from three aspects: interlayer intercalation, pseudocapacitance and surface adsorption, achieving a balance between intercalation capacity and surface adsorption capacity. The obtained sulfur-doped mesophase carbon microspheres have sodium storage behaviors mainly in surface adsorption and pseudocapacitance, and the capacitance control ratio is dominant, which is the key to its excellent rate performance.

[0029] The hierarchical porous carbon prepared by secondary sulfur doping with magnesium sulfate as the sulfur source is to expand the surface capacitance contribution on the basis of sacrificing the carbon interlayer spacing, and to utilize the SO4 2- With the -CH x It reacts mildly with CC bonds to form CSC covalent bonds (active carbon-sulfur bonds). Due to the abundance of active carbon-sulfur bonds, the first coulombic efficiency is instead through -SO x The selective removal of oxygen-containing functional groups and active carbon atoms by oxidation or S atom substitution reaction is significantly improved. At the same time, the pore-forming effect of the MgO crystal template formed by magnesium sulfate is used to realize the preparation of mesoporous hierarchical porous carbon with ultra-high sulfur doping amount. Mesoporous hierarchical porous carbon materials have the advantages of high specific surface area, excellent conductivity, physical and chemical stability, gas-liquid permeability, and adjustable pore structure. The obtained sulfur-doped mesophase carbon microsphere-based hierarchical porous carbon, whose surface sulfur-containing functional groups (active carbon-sulfur bonds CSC) undergo redox reactions with sodium ions, on the one hand, contributes rich pseudocapacitance, and on the other hand, obtains good rate and cycle performance by maintaining the structural stability of the soft carbon material during the cycle.

[0030] Tertiary sulfur doping is hard carbon coating soft carbon, using the room temperature polymerization characteristics of organic monomers to achieve uniform growth of hard carbon on the surface of soft carbon. EDOT is an organic sulfur-containing compound monomer, which can be synthesized into conductive polymer PEDOT by room temperature oxidative polymerization. The sulfur in it can provide abundant active sites for sodium ion storage. And PEDOT-based hard carbon materials have a large carbon layer spacing, which helps sodium ions to be reversibly embedded and removed between carbon layers. However, the sp2 carbon content of PEDOT-based hard carbon materials is limited, and the conductivity is poor.

[0031] Quadruple sulfur doping is to dope the outer shell with sulfur in the inner core, especially surface sulfur, under high temperature inert atmosphere, which not only widens the spacing between carbon layers but also makes full use of active sulfur-containing functional groups (active carbon-sulfur bonds CSC) to improve the performance of PEDOT-based hard carbon materials.

[0032] The method of the present invention can further achieve precise regulation of the carbon layer spacing (0.340-0.410nm), the sulfur doping amount (6.5-8.8at%) and the active carbon-sulfur bond CSC content (96-100%) by adjusting the addition amount of sulfur-doped mesophase carbon microspheres and the soft carbon carbonization temperature, thereby giving the soft and hard carbon composite materials a hybrid energy storage mechanism dominated by surface capacitance, thereby improving the first charge and discharge capacity, first efficiency and cycle performance of the sodium battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0034] Figure 1 This is a SEM image of the soft and hard carbon composite material of the present invention. DETAILED DESCRIPTION

[0035] In order to make the purpose, technical scheme and advantages of the present invention clearer, the technical scheme in the embodiment of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention. The process parameters of the following embodiments that do not specify specific conditions are usually based on conventional conditions.

[0036] The endpoints and any values ​​of the ranges disclosed in the present invention are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in the present invention.

[0037] The present invention provides a soft and hard carbon composite material and its preparation and application, which has the following implementation modes:

[0038] According to a first aspect of the present invention, a soft and hard carbon composite material has a core-shell structure of hard carbon coating soft carbon and being doubly sulfur-rich, wherein the soft carbon as the inner core is sulfur-doped mesophase carbon microsphere-based hierarchical carbon, and the hard carbon as the outer shell is sulfur-doped PEDOT-based hard carbon.

[0039] As an optional embodiment of the soft and hard carbon composite material described in the present invention, the carbon layer spacing of the soft and hard carbon composite material is 0.340-0.410nm (such as 0.345nm, 0.350nm, 0.355nm, 0.360nm, 0.365nm, 0.370nm, 0.375nm, 0.380nm, 0.385nm, 0.390nm, 0.395nm, 0.400nm, 0.405nm).

[0040] As an optional embodiment of the soft and hard carbon composite material of the present invention, the sulfur doping amount of the soft and hard carbon composite material is 6.5-8.8at% (such as 6.6at%, 6.8at%, 7.0at%, 7.2at%, 7.4at%, 7.6at%, 7.8at%, 8.0at%, 8.2at%, 8.4at%, 8.6at%).

[0041] As an optional embodiment of the soft and hard carbon composite material of the present invention, the content of active carbon-sulfur bonds CSC in the soft and hard carbon composite material accounts for 96% to 100% (such as 96.5%, 97%, 97.5%, 98%, 98.5%, 99%, 99.5%) of sulfur-containing organic bonds.

[0042] As an optional embodiment of the soft and hard carbon composite material of the present invention, the soft carbon is obtained by using sulfur-doped mesophase carbon microspheres obtained by etching the surface of mesophase carbon microspheres with H2S as a precursor, and then modified by sulfur-doping and pore adjustment with magnesium sulfate as a sulfur source template, and carbonized. Further optionally, the added mass ratio of magnesium sulfate to sulfur-doped mesophase carbon microspheres is 1 to 10:1 (such as 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1); and / or, the carbonization temperature is 600 to 890°C (such as 610°C, 630°C, 650°C, 670°C, 690°C, 710°C, 730°C, 750°C, 770°C, 790°C, 810°C, 830°C, 850°C, 870°C).

[0043] According to a second aspect of the present invention, a method for preparing the soft and hard carbon composite material as described in the first aspect comprises the following steps:

[0044] The soft carbon is prepared by using sulfur-doped mesophase carbon microspheres as a precursor, and then carbonized after being modified by sulfur doping and pore adjustment using magnesium sulfate as a sulfur source template, to obtain hierarchical porous carbon based on sulfur-doped mesophase carbon microspheres;

[0045] The soft and hard carbon composite material is obtained by using the soft carbon as the core, guiding the EDOT monomer to oxidatively polymerize on its surface, and then subjecting it to high-temperature inert carbonization, i.e., sulfur-doped PEDOT-based hard carbon;

[0046] The soft and hard carbon composite material has a core-shell structure in which hard carbon covers soft carbon and is doubly sulfur-rich.

[0047] Furthermore, the general preparation steps of the soft and hard carbon composite material may include the following:

[0048] S1. Preparation of sulfur-doped mesophase carbon microspheres

[0049] The preparation of sulfur-doped mesophase carbon microspheres is based on mesophase carbon microspheres as precursors, through pre-oxidation treatment and H2S gas etching. The specific steps may include:

[0050] S11, oxidizing the mesophase carbon microspheres in a mixed acid of nitric acid and sulfuric acid in a volume ratio of 1.5 to 2.5:1 (such as 1.6:1, 1.8:1, 2:1, 2.2:1, 2.4:1), washing with water until neutral, and then drying to obtain pre-oxidized mesophase carbon microspheres for standby use;

[0051] S12, the pre-oxidized mesophase carbon microspheres are loaded into a corundum boat and placed in a tube furnace, and high-temperature carbonization is performed in a mixed atmosphere of argon and hydrogen sulfide, and naturally cooled to room temperature to obtain sulfur-doped mesophase carbon microspheres. The specific high-temperature carbonization process can be as follows:

[0052] First, a pre-carbonization stage is carried out, in an argon atmosphere, the temperature is raised from room temperature to 350-450°C (such as 360°C, 380°C, 400°C, 420°C, 440°C) at a certain heating rate such as 2°C / min, and then kept warm for 0.5-1.5h (such as 0.6h, 0.8h, 1h, 1.2h, 1.4h);

[0053] Secondly, the carbonization stage is carried out in a mixed atmosphere (argon and hydrogen sulfide volume ratio of 8 to 10: 1 (such as 8.2: 1, 8.4: 1, 8.6: 1, 8.8: 1, 9: 1, 9.2: 1, 9.4: 1, 9.6: 1, 9.8: 1), and the temperature is raised from the pre-carbonization stage to 650 to 750 ° C (such as 660 ° C, 680 ° C, 700 ° C, 720 ° C, 740 ° C) at a certain heating rate such as 5 ° C / min and kept warm for 2-4h (such as 2.5 h, 3h, 3.5h), the gas flow rate of argon and hydrogen sulfide in the mixed atmosphere is 120-360ml / min (such as 130ml / min, 150ml / min, 170ml / min, 190ml / min, 210ml / min, 230ml / min, 250ml / min, 270ml / min, 290ml / min, 310ml / min, 330ml / min, 350ml / min).

[0054] In the present invention, mesocarbon microbeads (MCMB) are micron-sized spherical carbon materials having a nematic liquid crystal layered stacking structure generated by thermal polycondensation of heavy aromatic compounds such as asphalt.

[0055] S2. Preparation of soft and hard carbon composites

[0056] S21. Preparation and pretreatment of soft carbon

[0057] Sulfur-doped mesophase carbon microspheres are added to DMF solvent for ultrasonic dispersion. Then magnesium sulfate is added, and the mass ratio of magnesium sulfate to sulfur-doped mesophase carbon microspheres is 1 to 10:1 (such as 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1), magnetic stirring is performed, and then the solvent is evaporated in a rotary evaporator to obtain a solid. The solid is loaded into a corundum boat and placed in a tube furnace, and high-temperature carbonization is performed under an inert gas such as nitrogen atmosphere. The carbonization process is heated from room temperature to a specified carbonization temperature at a certain heating rate such as 5°C / min and kept warm. The carbonization temperature is 600°C-890°C (such as 610°C, 630°C, 650°C, 670°C, 690°C, 710°C, 730°C, 750°C, 770°C, 790°C, 810°C, 830°C, 850°C, 870°C). After naturally cooling to room temperature, soft carbon, i.e., sulfur-doped mesophase carbon microsphere-based hierarchical porous carbon, is obtained. The soft carbon is acid-washed and dried to obtain pretreated soft carbon. Acid washing is necessary to remove inorganic metal salts and other acid-soluble impurities.

[0058] S22. Preparation of soft and hard carbon composites

[0059] Sodium dodecylbenzene sulfonate is dissolved in deionized water, and EDOT monomer and pretreated soft carbon are added in sequence, with a mass ratio of 1-20:80-99, specifically, typically but not limitedly, 2:98, 3:97, 4:96, 5:95, 6:94, 7:93, 8:92, 9:91, 10:90, 11:89, 12:88, 13:87, 14:86, 15:85, 16:84, 17:83, 18:82, 19:81), and stirring is continued for a certain time, such as 30 minutes, to obtain a mixed solution; a chain initiator such as ammonium persulfate is dissolved in water, and the mixture is stirred for 30 minutes. The obtained mixture is dissolved in deionized water and added dropwise to the mixed solution; after polymerization at room temperature for a certain period of time, such as 24 hours, the mixture is centrifuged and washed with deionized water until it is colorless, and then dried to obtain a black powder; the dried black powder is loaded into a corundum boat and placed in a tubular furnace, and heated to a certain high temperature, such as 700°C, at a certain heating rate under an argon or nitrogen atmosphere, and carbonized for a certain period of time, and then naturally cooled to room temperature to obtain a hard and soft carbon composite material of hard carbon coated with soft carbon, that is, a soft carbon with a core of sulfur-doped mesophase carbon microsphere-based hierarchical porous carbon, and a shell of sulfur-doped PEDOT-based hard carbon, and both the core and the shell are sulfur-rich.

[0060] In the present invention, PEDOT is a polymer of EDOT (3,4-ethylenedioxythiophene monomer), and the molecular structure is as follows:

[0061] Wherein, R is hydrogen.

[0062] PEDOT has the characteristics of simple molecular structure, small energy gap and high conductivity.

[0063] The soft and hard carbon composite materials of the present invention achieve an improvement in sodium storage capacity through surface chemical modification, pore structure regulation and soft and hard carbon composites. It can not only obtain considerable intercalation capacity by virtue of the widened carbon layer spacing, but also obtain abundant sodium storage sites to achieve a large proportion of surface capacitance storage.

[0064] First, the sodium storage capacity of the asphalt-based soft carbon anode is improved by surface chemical modification. Asphalt-based mesophase carbon microspheres are selected as precursors. First, they have a spherical structure and are easy to disperse in the slurry. When the current passes through the anode surface, they can be evenly distributed; second, they can reduce the consumption of sodium ions at sharp material edges and irregular morphologies to avoid excessive growth of SEI; third, their larger packing density can obtain higher volume energy. The active sulfur element is introduced into the surface of the mesophase carbon microspheres by H2S gas etching to perform surface chemical modification (one-time sulfur doping) in order to improve the sodium storage capacity of the mesophase carbon microspheres while ensuring the first coulomb efficiency. The present invention does not make special requirements on the particle size of the mesophase carbon microspheres. The specific particle size of the mesophase carbon microspheres can be selected between 2-20μm, and typically but not restrictively can be selected as 3μm, 5μm, 7μm, 9μm, 11μm, 13μm, 15μm, 17μm, and 19μm.

[0065] Secondly, from the perspective of pore structure regulation to improve sodium storage capacity, a suitable hard template is selected to prepare mesopore-dominated hierarchical porous carbon. Specifically, mesophase carbon microspheres (sulfur-doped mesophase carbon microspheres) etched by H2S gas are used as precursors, and magnesium sulfate is selected as both a template and a sulfur source to prepare secondary sulfur-doped sulfur-doped mesophase carbon microsphere-based hierarchical porous carbon, in order to achieve a simultaneous increase in interlayer intercalation capacity, pseudocapacitance contribution, and surface adsorption energy storage through increased sulfur content and mesoporous structure. Specifically, by utilizing SO4 2- With the -CH x The CC bond reacts mildly to form a CSC covalent bond (activated carbon-sulfur bond), and at the same time, the pore-forming effect of the MgO crystal template formed by magnesium sulfate is used to prepare hierarchical porous carbon dominated by mesopores with ultra-high sulfur doping. Hierarchical porous carbon is mesoporous and has the advantages of high specific surface area, excellent conductivity, physical and chemical stability, gas-liquid permeability, and adjustable pore structure. In addition, its surface sulfur-containing functional groups (activated carbon-sulfur bonds CSC) undergo redox reactions with sodium ions, which contribute abundant pseudocapacitance on the one hand, and obtain good rate and cycle performance on the other hand by maintaining the structural stability of the soft carbon material during the cycle.

[0066] Finally, the soft and hard carbons are composited, and the sulfur-doped mesophase carbon microsphere-based hierarchical carbon and EDOT organic sulfur-containing compound monomers are oxidatively polymerized and carbonized at high temperature inertly to prepare soft and hard carbon composite materials. During oxidative polymerization, the sulfur-doped mesophase carbon microsphere-based hierarchical carbon (sulfur-containing soft carbon) is used as the polymerization center to guide EDOT to polymerize layer by layer on its surface into a shell, and sulfur is doped three times while constructing a core-shell structure. During high-temperature inert carbonization, the construction of the core-shell structure enables the sulfur element on the surface of the sulfur-containing soft carbon at high temperature to escape in the form of gas, but due to the inert atmosphere, the sulfur element is not completely converted into volatile sulfur-containing substances, but the external carbon shell is sulfur-doped four times, providing additional active sulfur-containing functional groups (active carbon-sulfur bonds CSC) for PEDOT-based hard carbon while widening the carbon layer spacing, and finally forming a dual sulfur-rich soft and hard carbon composite material with sulfur-doped mesophase carbon microsphere-based hierarchical carbon as the core, layer-by-layer cross-linking, and sulfur-doped PEDOT-based hard carbon as the shell. Sulfur-doped mesophase carbon microspheres have a hierarchical carbon core and rich graphite crystals that contribute to good conductivity. At the same time, sulfur-doping of the outer carbon shell is achieved, which can not only provide additional active carbon-sulfur bonds to increase the contribution of pseudocapacitance, but also widen the carbon layer spacing and improve the intercalation capacity; the outer carbon shell presents a layer-by-layer cross-linked structure, and the soft and hard carbons are in close contact, allowing the electrolyte ions to migrate quickly.

[0067] In the process of preparing the soft and hard carbon composite materials of the present invention, the inventors have found through extensive research that different sulfur doping methods lead to different sodium storage mechanisms. Sulfur doping by H2S etching can significantly improve the carbon interlayer spacing, sp2 carbon content and sulfur doping amount. Although the first coulomb efficiency is slightly reduced, the sodium storage performance is significantly improved in three aspects: interlayer intercalation, pseudocapacitance and surface adsorption, achieving a balance between intercalation capacity and surface adsorption capacity. The hierarchical porous carbon prepared with magnesium sulfate as the sulfur source expands the contribution of surface capacitance on the basis of sacrificing the carbon interlayer spacing. Due to the rich active carbon sulfur bonds, the first coulomb efficiency is instead improved by -SO xThe selective removal of oxygen-containing functional groups and active carbon atoms by oxidation or S atom substitution reaction is significantly improved. When PEDOT-based hard carbon materials are coated with soft carbon, the sulfur in PEDOT can provide abundant active sites for sodium ion storage, and has a large carbon layer spacing, which is conducive to the reversible embedding and extraction of sodium ions between carbon layers. In addition, during high-temperature inert carbonization, the escape of the inner core sulfur, especially the sulfur on the surface of the inner core, sulfur dopes the outer shell, widens the carbon layer spacing and makes full use of the active carbon-sulfur bond CSC, thereby improving the performance of PEDOT-based hard carbon materials. Finally, by adjusting the addition amount of sulfur-doped mesophase carbon microspheres and the carbonization temperature, the carbon layer spacing (0.340-0.410nm), sulfur doping amount (6.5-8.8at%) and active carbon-sulfur bond CSC content (96-100%) of the soft and hard carbon composites can be precisely regulated, giving the soft and hard carbon composites a hybrid energy storage mechanism dominated by surface capacitance, so that the first charge and discharge capacity, first efficiency and cycle performance of the sodium battery are improved. Therefore, the soft and hard carbon composite material of the present invention is used as a sodium battery negative electrode material, which can significantly improve the initial charge and discharge capacity, initial efficiency and cycle performance of the sodium battery.

[0068] The present invention will be further described below with reference to specific embodiments and comparative examples.

[0069] The sulfur-doped mesophase carbon microspheres involved in the examples and comparative examples are prepared as follows:

[0070] S11, oxidizing mesophase carbon microspheres with a particle size of 8-15 μm in a mixed acid of nitric acid and sulfuric acid in a volume ratio of 2:1, washing with water until neutral, and then drying to obtain pre-oxidized mesophase carbon microspheres for standby use;

[0071] S12. The pre-oxidized mesophase carbon microspheres are loaded into a corundum boat and placed in a tubular furnace. First, a pre-carbonization stage is performed in an argon atmosphere, the temperature is increased from room temperature to 400°C and then kept for 1 hour at a heating rate of 2°C / min. Secondly, a carbonization stage is performed in a mixed atmosphere (argon and hydrogen sulfide volume ratio is 9:1), the temperature is increased from 400°C to 700°C at a heating rate of 5°C / min and kept for 3 hours. The gas flow rate of argon and hydrogen sulfide in the mixed atmosphere is 240 ml / min. Finally, the mixture is naturally cooled to room temperature to obtain sulfur-doped mesophase carbon microspheres.

[0072] Example 1

[0073] 4g of sulfur-doped mesophase carbon microspheres were added to 400ml of DMF solvent and ultrasonically dispersed for 30min. Then 20g of magnesium sulfate was added, magnetically stirred for 12h, and then placed in a rotary evaporator to evaporate the solvent. The solid was loaded into a corundum boat and placed in a tube furnace for high-temperature carbonization under a nitrogen atmosphere. The carbonization process was heated from room temperature to the specified carbonization temperature at a heating rate of 5℃ / min and kept warm for 1h. The carbonization temperature was 600℃. After naturally cooling to room temperature, soft carbon, i.e., hierarchical porous carbon based on sulfur-doped mesophase carbon microspheres, was obtained. The soft carbon was acid-washed and dried to obtain pretreated soft carbon.

[0074] 5g of sodium dodecylbenzene sulfonate was dissolved in 50ml of deionized water, and 1ml of EDOT monomer and pretreated soft carbon material (the mass ratio of EDOT monomer to pretreated soft carbon was 10:90) were added in sequence, and stirring was continued for 30min; 4g of ammonium persulfate was dissolved in 10ml of deionized water, and added dropwise to the above mixed solution; after polymerization at room temperature for 24h, the mixture was centrifuged and washed with deionized water until colorless, and dried to obtain a black powder; the dried black powder was loaded into a corundum boat and placed in a tubular furnace, and carbonized at 700℃ for 2h under argon or nitrogen atmosphere with a heating rate of 3℃ / min, and naturally cooled to room temperature to obtain a soft and hard carbon composite material of hard carbon coated with soft carbon, that is, a soft carbon with a core of sulfur-doped mesophase carbon microsphere-based hierarchical porous carbon, and a shell of sulfur-doped PEDOT-based hard carbon, and both the core and the shell were sulfur-rich.

[0075] Example 2

[0076] 4g of sulfur-doped mesophase carbon microspheres were added to 400ml of DMF solvent and ultrasonically dispersed for 30min. Then 20g of magnesium sulfate was added, magnetically stirred for 12h, and then placed in a rotary evaporator to evaporate the solvent. The solid was loaded into a corundum boat and placed in a tubular furnace for high-temperature carbonization under a nitrogen atmosphere. The carbonization process was heated from room temperature to the specified carbonization temperature at a heating rate of 5℃ / min and kept warm for 1h. The carbonization temperature was 650℃. After naturally cooling to room temperature, soft carbon, i.e., hierarchical porous carbon based on sulfur-doped mesophase carbon microspheres, was obtained. The soft carbon was acid-washed and dried to obtain pretreated soft carbon.

[0077] 5g of sodium dodecylbenzene sulfonate was dissolved in 50ml of deionized water, and 1ml of EDOT monomer and pretreated soft carbon material (the mass ratio of EDOT monomer to pretreated soft carbon was 10:90) were added in sequence, and stirring was continued for 30min; 4g of ammonium persulfate was dissolved in 10ml of deionized water, and added dropwise to the above mixed solution; after polymerization at room temperature for 24h, the mixture was centrifuged and washed with deionized water until colorless, and dried to obtain a black powder; the dried black powder was loaded into a corundum boat and placed in a tubular furnace, and carbonized at 700℃ for 2h under argon or nitrogen atmosphere with a heating rate of 3℃ / min, and naturally cooled to room temperature to obtain a soft and hard carbon composite material of hard carbon coated with soft carbon, that is, a soft carbon with a core of sulfur-doped mesophase carbon microsphere-based hierarchical porous carbon, and a shell of sulfur-doped PEDOT-based hard carbon, and both the core and the shell were sulfur-rich.

[0078] Example 3

[0079] 4g of sulfur-doped mesophase carbon microspheres were added to 400ml of DMF solvent and ultrasonically dispersed for 30min. Then 20g of magnesium sulfate was added, magnetically stirred for 12h, and then placed in a rotary evaporator to evaporate the solvent. The solid was loaded into a corundum boat and placed in a tube furnace for high-temperature carbonization under a nitrogen atmosphere. The carbonization process was heated from room temperature to the specified carbonization temperature at a rate of 5℃ / min and kept warm for 1h. The carbonization temperature was 700℃. After naturally cooling to room temperature, soft carbon, i.e., hierarchical porous carbon based on sulfur-doped mesophase carbon microspheres, was obtained. The soft carbon was acid-washed and dried to obtain pretreated soft carbon.

[0080] 5g of sodium dodecylbenzene sulfonate was dissolved in 50ml of deionized water, and 1ml of EDOT monomer and pretreated soft carbon material (the mass ratio of EDOT monomer to pretreated soft carbon was 10:90) were added in sequence, and stirring was continued for 30min; 4g of ammonium persulfate was dissolved in 10ml of deionized water, and added dropwise to the above mixed solution; after polymerization at room temperature for 24h, the mixture was centrifuged and washed with deionized water until colorless, and dried to obtain a black powder; the dried black powder was loaded into a corundum boat and placed in a tubular furnace, and carbonized at 700℃ for 2h under argon or nitrogen atmosphere with a heating rate of 3℃ / min, and naturally cooled to room temperature to obtain a soft and hard carbon composite material of hard carbon coated with soft carbon, that is, a soft carbon with a core of sulfur-doped mesophase carbon microsphere-based hierarchical porous carbon, and a shell of sulfur-doped PEDOT-based hard carbon, and both the core and the shell were sulfur-rich.

[0081] Examples 4-6 and Comparative Examples 1-2

[0082] The difference from Example 3 is that the carbonization temperatures are different only during the soft carbon treatment, which are 750° C., 800° C., 850° C., 900° C., and 950° C. The rest of the settings are the same as those in Example 3.

[0083] Comparative Example 3

[0084] 4g of sulfur-doped mesophase carbon microspheres were added to 400ml of DMF solvent and ultrasonically dispersed for 30min. Then 20g of magnesium sulfate was added, magnetically stirred for 12h, and then placed in a rotary evaporator to evaporate the solvent. The solid was loaded into a corundum boat and placed in a tube furnace for high-temperature carbonization under a nitrogen atmosphere. The carbonization process was heated from room temperature to the specified carbonization temperature at a heating rate of 5℃ / min and kept warm for 1h. The carbonization temperature was 700℃. After naturally cooling to room temperature, hierarchical porous carbon based on sulfur-doped mesophase carbon microspheres was obtained, which was acid-washed and dried to obtain soft carbon.

[0085] Comparative Example 4

[0086] 4g of mesophase carbon microspheres were added to 400ml of DMF solvent and ultrasonically dispersed for 30min. Then 20g of magnesium sulfate was added, magnetic stirring was carried out for 12h, and then the solvent was evaporated in a rotary evaporator. The solid was loaded into a corundum boat and placed in a tube furnace for high-temperature carbonization under a nitrogen atmosphere. The carbonization process was heated from room temperature to the specified carbonization temperature at a heating rate of 5℃ / min and kept warm for 1h. The carbonization temperature was 700℃. After naturally cooling to room temperature, soft carbon was obtained by acid washing and drying.

[0087] Comparative Example 5

[0088] 4g of mesophase carbon microspheres were added to 400ml of DMF solvent and ultrasonically dispersed for 30min. Then 20g of magnesium sulfate was added, magnetically stirred for 12h, and then placed in a rotary evaporator to evaporate the solvent. The solid was loaded into a corundum boat and placed in a tube furnace for high-temperature carbonization under a nitrogen atmosphere. The carbonization process was heated from room temperature to the specified carbonization temperature at a heating rate of 5℃ / min and kept warm for 1h. The carbonization temperature was 700℃. After naturally cooling to room temperature, the pretreated soft carbon was obtained by acid washing and drying.

[0089] Dissolve 5g of sodium dodecylbenzene sulfonate in 50ml of deionized water, add 1ml of EDOT monomer and pretreated soft carbon material (the mass ratio of EDOT monomer to pretreated soft carbon is 10:90) in sequence, and continue stirring for 30min; dissolve 4g of ammonium persulfate in 10ml of deionized water and add dropwise to the above mixed solution; after polymerizing at room temperature for 24h, centrifuge the mixture and wash it with deionized water until it is colorless, and dry it to obtain a black powder; put the dried black powder into a corundum boat and place it in a tubular furnace, carbonize it at 700℃ for 2h under argon or nitrogen atmosphere, with a heating rate of 3℃ / min, and naturally cool it to room temperature to obtain a soft and hard carbon composite material.

[0090] Tests and Results

[0091] The carbon materials obtained in the examples and comparative examples were tested as follows:

[0092] (1) Carbon interlayer spacing test: XRD data were obtained by X-ray diffraction test, with a Cu target wavelength λ = 0.154056 nm and a diffraction angle 2θ of 10-90°. The carbon interlayer spacing was calculated by substituting the diffraction angle (002) of XRD into the Scherrer formula.

[0093] (2) Sulfur content test: elemental analysis was performed using energy dispersive X-ray spectroscopy (EDS) on a field emission scanning electron microscope.

[0094] (3) CSC content test: using infrared combined with carbon and sulfur analyzer for analysis.

[0095] The carbon material obtained in the embodiment and the comparative example is used as the negative electrode material of the sodium battery, and is coated with a conductive agent, sodium carboxymethyl cellulose (CMC), and styrene-butadiene rubber (SBR) in a mass percentage of 94.5:2:1.5:2 as the negative electrode. The metal sodium sheet is the positive electrode, the diaphragm is a glass fiber diaphragm, the sodium salt in the electrolyte is NaPF6 with a concentration of 1.5M, the solvent is EC and DMC in a volume ratio of 1:1, and there is 5% volume of the additive EMC. The battery is installed in a glove box filled with argon, and then a charge and discharge test is carried out in a blue electric test cabinet. The charge and discharge rate is 0.1C (voltage range 0-2V), and the nominal capacity is set to 320mAh / g. The first charge and discharge capacity, the first coulomb efficiency (first efficiency), and the capacity retention rate after 100 cycles are recorded. The first efficiency is the ratio of the first discharge capacity to the first charge capacity.

[0096] The test results are shown in Table 1.

[0097] Table 1

[0098]

[0099]

[0100] By comparing the embodiments with the comparative examples, it can be seen that the soft and hard carbon composite materials of the present invention, whose inner core is soft carbon of sulfur-doped mesophase carbon microsphere-based hierarchical carbon and whose outer shell is sulfur-doped PEDOT-based hard carbon, achieve improvements in the first charge and discharge capacity, first efficiency and cycle retention rate of the sodium battery. This should be the result of achieving an increase in the sodium storage capacity of the mesophase carbon microspheres, which may be due to the considerable intercalation capacity obtained by widening the carbon layer spacing, and the acquisition of abundant sodium storage sites to achieve a large proportion of surface capacitance storage, thereby improving the first charge and discharge capacity, first efficiency and cycle performance of the sodium battery.

[0101] By comparing Examples 1-6 and Comparative Examples 1-2, it can be seen that when the soft and hard carbon composite materials of the present invention and the sulfur-doped mesophase carbon microsphere-based hierarchical carbon are carbonized, as the temperature increases, the first charge and discharge capacity, first efficiency and 100-cycle retention rate of the sodium battery first increase and then decrease, especially at 700°C (Example 3), reaching the highest, which are 335mAh / g, 290.1mAh / g, 86.6%, and 99.1%, respectively, while at 900°C and thereafter, they are significantly reduced to 305mAh / g, 240mAh / g, 80%, and below 91%.

[0102] By comparing Example 3 with Comparative Example 3, and by comparing Comparative Examples 4 and 5, it can be seen that after the soft and hard carbon are composited, the first charge and discharge capacity, first efficiency and cycle retention rate of the sodium battery are improved, and the soft and hard carbon composite material of the present invention has more significant improvements, especially the first efficiency and cycle retention rate. Further, by comparing the total amount of sulfur doping and the amount of sulfur doping in the core, it can be seen that the construction of the core-shell structure not only introduces more sulfur through the shell, but also unexpectedly realizes the re-sulfur doping of the sulfur-containing soft carbon core to the PEDOT-based hard carbon shell at high temperature, providing additional active carbon-sulfur bonds CSC for the PEDOT-based hard carbon while widening the carbon layer spacing.

[0103] By comparing Example 3 with Comparative Examples 4 and 5, and by comparing Comparative Examples 3 and 4, it can be seen that for the modification of mesophase carbon microspheres, the present invention uses hydrogen sulfide etching for surface modification, sulfur doping for the first time, magnesium sulfate for pore formation and adjustment, sulfur doping for the second time, hard carbon coating soft carbon for the third time, and high temperature inert environment for the fourth time of sulfur doping of the core to the shell. The four times of sulfur doping improvement are more effective, so that the sodium battery has better first charge and discharge capacity, first efficiency and cycle retention rate. This is because: sulfur doping by H2S etching can achieve a significant increase in carbon interlayer spacing, sp2 carbon content and sulfur doping amount. Although the first coulomb efficiency is slightly reduced, the sodium storage performance is significantly improved in terms of interlayer intercalation, pseudocapacitance and surface adsorption, achieving a balance between intercalation capacity and surface adsorption capacity. The hierarchical porous carbon prepared with magnesium sulfate as the sulfur source expands the surface capacitance contribution on the basis of sacrificing the carbon interlayer spacing. Due to the rich active carbon sulfur bonds, the first coulomb efficiency is instead increased by -SO x The selective removal of oxygen-containing functional groups and active carbon atoms by oxidation or S atom substitution reaction is significantly improved. When hard carbon is coated with soft carbon, the sulfur in PEDOT can provide abundant active sites for sodium ion storage, and has a large carbon layer spacing, which helps the sodium ions to be reversibly embedded and removed between carbon layers. In addition, during high-temperature inert carbonization, the escape of sulfur in the inner core, especially sulfur on the surface of the inner core, can dope the outer shell with sulfur, which can make full use of the active carbon-sulfur bond CSC while widening the carbon layer spacing to improve material properties.

[0104] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A soft and hard carbon composite material, characterized in that: The soft and hard carbon composite material has a core-shell structure of hard carbon covering soft carbon and being double-sulfur-rich. The soft carbon as the core is sulfur-doped mesophase carbon microsphere-based hierarchical carbon, and the hard carbon as the shell is sulfur-doped PEDOT-based hard carbon.

2. The soft and hard carbon composite material according to claim 1, characterized in that: The carbon interlayer spacing of the soft and hard carbon composite material is 0.340-0.410 nm; and / or, the sulfur doping amount of the soft and hard carbon composite material is 6.5 to 8.8 at %; And / or, the content of active carbon-sulfur bonds (CSC) in the soft and hard carbon composite material accounts for 96-100% of the sulfur-containing organic bonds.

3. The soft and hard carbon composite material according to claim 1, characterized in that: The soft carbon is obtained by using sulfur-doped mesophase carbon microspheres obtained by etching the surface of mesophase carbon microspheres with H2S as a precursor, and then being modified by sulfur-doping and pore adjustment using magnesium sulfate as a sulfur source template and carbonizing.

4. The soft and hard carbon composite material according to claim 3, characterized in that: The added mass ratio of the magnesium sulfate to the sulfur-doped mesophase carbon microspheres is 1 to 10:1; and / or the carbonization temperature is 600 to 890°C.

5. A method for preparing a soft and hard carbon composite material as claimed in any one of claims 1 to 4, characterized in that: The following steps are involved: The soft carbon is prepared by using sulfur-doped mesophase carbon microspheres as a precursor, and then carbonized after being modified by sulfur doping and pore adjustment using magnesium sulfate as a sulfur source template, to obtain hierarchical porous carbon based on sulfur-doped mesophase carbon microspheres; The soft and hard carbon composite material is obtained by using the soft carbon as the core, guiding the EDOT monomer to oxidatively polymerize on its surface, and then subjecting it to high-temperature inert carbonization, i.e., sulfur-doped PEDOT-based hard carbon; The soft and hard carbon composite material has a core-shell structure in which hard carbon covers soft carbon and is doubly sulfur-rich.

6. The method for preparing the soft and hard carbon composite material according to claim 5, characterized in that: The sulfur-doped mesophase carbon microspheres are prepared by using mesophase carbon microspheres as precursors through pre-oxidation treatment and H2S gas etching.

7. The method for preparing the soft and hard carbon composite material according to claim 5, characterized in that: When the soft carbon is prepared, the added mass ratio of the magnesium sulfate to the sulfur-doped mesophase carbon microspheres is 1 to 10:

1.

8. The method for preparing the soft and hard carbon composite material according to claim 5, characterized in that: When the soft and hard carbon composite material is prepared, the added mass ratio of the EDOT monomer to the soft carbon is 1-20:80-99.

9. A sodium negative electrode material, characterized in that: It comprises the soft or hard carbon composite material as claimed in any one of claims 1 to 4 or the soft or hard carbon composite material prepared by the preparation method as claimed in any one of claims 5 to 8.

10. A sodium ion battery, characterized in that: It comprises the soft or hard carbon composite material as claimed in any one of claims 1 to 4 or the soft or hard carbon composite material prepared by the preparation method as claimed in any one of claims 5 to 8.

Citation Information

Patent Citations

  • Graphite negative electrode material and preparation method and application thereof

    CN116169289A

  • Negative electrode material and preparation method and application thereof

    CN117712350A

  • Composite lithium manganate positive electrode material, preparation method thereof and lithium ion battery

    CN117810418A

  • Multivalent Metal Ion Battery Having a Cathode of Recompressed Graphite Worms and Manufacturing Method

    US20180269479A1

  • Preparation method for sodium ion battery porous hard carbon material, and product and use thereof

    WO2024000885A1

Cited By

  • Negative electrode material and preparation method thereof, negative electrode plate and sodium battery

    CN121922620A